The Effect of Job Demands-Resources and Work-Life Balance on Organizational Commitment through Job Satisfaction as a Mediator Variable (Study on South Kuta Sector Police Personnel): A Research Proposal - Faizal, Reza Ahmad (Advances in Social Sciences Research Journal, 2021)
The purpose of this research is to propose the research model to determine the predictors of job satisfaction and organizational commitment. The proposed model has three independent variables, which are job demands resources, work-life balance, job satisfaction and one dependent variable, which is organizational commitment. Independent variable leads to mediating variable, which is job satisfaction as dependent variable predictor. The proposed research model has five hypotheses determining whether job demands resources, work-life balance and job satisfaction affect organizational commitment. The research will be carried out at South Kuta Sector Police. This research is the first one in providing the proposed model to know the organizational commitment in sector police in Bali. The empirical findings will be useful as reference for further study and policy making about human resources.